Scalable model of a CHP unit for HIL simulation of a smart combined grid system - Griese, Martin; Pawlik, Thomas; Schulte, Thomas; Maas, Jürgen
Due to the increasing energy demand and shortage of fossil fuels, the energy systems will be transformed from mainly centralized into more decentralized systems, also incorporating more renewable energy. However, optimizing the control and structure of these systems is rather complex. A method for analyzing and planning of such systems is an adapted variant of the so called Hardware-in-the-Loop simulation. This approach comprises virtual energy components as models combined with data from experimental components. As a virtual energy component, a simulation model describing the physical behavior of CHP units is proposed in this contribution. The modeling approach is based on a time domain approach using state variables of the multiple domains to describe the dynamic behavior. For instance, the first law of thermodynamics is applied to model the thermal quantities. Furthermore, the model is scalable regarding the modeling depth and the power ratings which allows an application for different simulation scenarios. Finally, the overall model is parameterized and validated with data of a medium sized CHP plant.